On the benefits of nominal appreciations: Contrasting evidence across developed and developing countries - Magda Kandil (Borsa Istanbul Review, 2015)
The paper studies determinants of flexibility of the nominal effective exchange rate and the effects of exchange rate shocks on macroeconomic variables and key components of the external balances using data for a sample of advanced and developing countries. The composite evidence points to the positive effects of appreciation through cheaper imports in support of higher growth and lower price inflation in advanced and developing countries. However, the negative effects of appreciation are more pervasive on the external balances in developing countries. The implication is developing countries remain highly dependent on exports of commodities. In contrast, advanced countries are more diversified and ahead in capitalizing on currency appreciation to mobilize investment growth, a channel that boosts competitiveness and mitigates the adverse effect of appreciation on external stability. The evidence attests to the need to create an environment that is more conducive to investment growth in developing countries.